ผลของตัวเร่งปฏิกิริยาต่อคุณภาพของน้ำมันชีวภาพจากไพโรไลซิสชิ้นไม้ยูคาลิปตัสและซังข้าวโพดในเครื่องปฏิกรณ์เบดนิ่ง - วรเวช ศรีปราโมช (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This research was focused on the optimal conditions for pyrolysis of eucalyptus woodchips and corncob in fixed-bed reactor. The study found that the optimal conditions for both biomasses included 30 mins of reaction time, 500˚C for temperature, and 0.50 - 0.71 mm for biomass particle size. Besides, the optimal nitrogen flow rate was 120 ml/min for eucalyptus and 80 ml/min for corncob. These conditions provided the maximum bio-oil yield for both eucalyptus and corncob at 31.69 %wt. and 22.01 %wt., respectively. In addition, bio-oil from both biomasses had increasing heating value, the number are similar which were 23.14 MJ/kg for eucalyptus and 23.27 MJ/kg for corncob. This finding was consistent with lower H/C ratio and O/C ratio in bio-oil comparing to ratios in particle from both biomasses. According to composition analysis of bio-oil, the most composition was Phenols group, the second was carboxylic acids, aldehyde, ethers, ketones, Hydrocarbon, saccharide and the least was Furans. Moreover, studying the effect of dolomite and FCC spent catalysts on pyrolysis’s product yield found that the optimal amount of each catalyst was 5 %wt. for each biomass. Besides, these catalysts had no significant impact on reducing oxygen in bio-oil.